Isolation of biologically active plant secondary metabolites in Albizia chevalieri using column chromatographic techniques (Journal of Pure and Applied Sciences (Science Forum), 2026)
Plants have served human beings as a natural source for treatments and therapies from ancient times to date; among them, medicinal herbs have gained attention because of its wide use and less side effects. Chromatographic techniques have a significant role in natural products chemistry and also contribute dramatically to the discovery of novel and innovative compounds of pharmaceutical and biomedical importance. In the present study, the phytochemical analysis of Albizia chevalieri was carried out for the three aerial parts of the plant extracted with three different solvents (methanol, ethyl acetate, and n-hexane). This study also focused on a step-by-step visual demonstration of fractionation and isolation of biologically active plant secondary metabolites in A. chevalieri using column chromatographic techniques. Isolation of bioactive compounds using column chromatography involves preparation of the sample; packing of column; pouring of sample into the column; elution of fractions, and analysis of each fractions using thin layer chromatography. Based on the column chromatographic technique, it was observed that in each fraction one band were detected. Qualitative analysis showed that methanol extracted almost all the secondary metabolites in all the three aerial parts of the plant. After quantification, it was observed that methanol root extract had the highest phenolic contents [44.83 µg garlic acid equivalent (GAE)/g], followed by methanol leaf extract (38.89 µg GAE/g) and methanol stem bark extract (22.00 µg GAE/g). Root ethyl acetate extract (8.19 µg GAE/g), stem bark ethyl acetate extract (13.49 µg GAE/g), and leaves ethyl acetate extract (23.66 µg/GAE/g) followed through, while n-hexane extracts were having a very low phenolic content with n-hexane root (0.66 µg GAE/g), n-hexane stem bark extract (2.69 µg GAE/g), and n-hexane leaves extract (7.80 µg GAE/g). The presence of a high amount of phytochemical compounds suggests that the A. chevalieri plant has a high medicinal value and can be carefully studied to extract the natural compounds which are beneficial to human beings and that could be commercialized for higher production than using synthetic drugs with side effects. However, depending on the nature of research, compounds can be further purified using high-performance liquid chromatography, and nuclear magnetic resonance spectral analyses.